Trends and Tendencies of Uni-dimensional Poverty is not the Flip Side of Poverty - Raza, Qasim; Saboor, Abdul; Hameed, Gulnaz; Hashmi, Naimatullah (Pakistan Journal of Humanities and Social Sciences, 2023)
This study focused on trends and tendencies of Unidimesnional poverty in overall Pakistan, not only at the national level but also at the provincial and regional level. The FGT methodology was applied to measuring poverty by using PSLM data from 2010–11 and 2019–20. The empirical results show that, while absolute poverty has gone down over the past ten years, relative poverty has gone up in a number of places. Compared to urban areas, rural areas are more likely to see increasing rates of relative poverty. Income disparity is on the rise in the cities of Punjab and KPK compared to the countryside, and the reverse is true in Sindh and Baluchistan. In Punjab and KPK, the trend and tendencies of income inequality are greater in cities than in rural areas, whereas the opposite is true in Sindh and Baluchistan. Further, this study finds out that poverty in Pakistan is not only a monetary phenomenon but also an intellectual one. Therefore, if we focus only on the monetary side of poverty to eradicate it, it will not be possible to eradicate it by 2030, intellectual poverty is actually the flip side of poverty.